An Investıgatıon On Influence Of Anterıor Reposıtıonıng Splınt In The Treatment Of Temporomandıbular Joınt Wıth Recıprocal Clıckıng - Ahmet Keskin; Adnan Öztürk (Galenos Yayinevi, 1992)
The anterior repositioning splint is used to treat temporomandibular joint with reciprocal clicking. In this study anterior repositioning splint was compared to a normal positioning splint and to an untreated control group. Anterior repositioning splint was much more effective on elimination of reciprocal clicking than normal splint. No stasistically significant differences were found between two splint groups by the reduction and elimination of palpatory tenderness of the TMJ and masticatory muscles. There was recurrence in most of the patients from the standpoint of pain, clicking, and tenderness following removal of the splint.